Hydrogel-biochar composite for sorption of arsenic and zinc from aqueous media. - Sanyang, Lamin (2013)
Arsenic and zinc contaminated water is an environmental issue due to their toxicity. Acute arsenic poisoning has claimed the lives of many and causes adverse health risk to millions of people (i.e. Bangladesh, India, China etc.). Although, zinc is a vital element for human growth but its excessive intake may pose harm to the environment and public health. Effective removal of these contaminants can be obtained by adsorbing them onto low cost adsorbents. In this study, hydrogel-biochar composite (HBC-RH) was prepared using acrylamide (AAm) as monomer, with N.N’-methylenebisacrylamide (MBA) as crosslinker, ammonium persulfate (APS) as initiator and rice husk biochar (RHB). The synthesized hydrogel-biochar composites were characterized (swelling behavior, surface morphology, functional group, surface area and porosity) and utilized for the removal of arsenic and zinc from aqueous media. Batch equilibrium and kinetic studies were conducted to investigate the potential of the hydrogel-biochar composites on arsenic and zinc removal. The optimum experimental conditions for this study were determined by evaluating the effect of solution pH (4 – 10), adsorbent dosage (0.167 – 10g/L),adsorbate initial concentration (1 – 150mg/L) and contact time (0 – 48hrs). From the experimental results obtained, HBC-RH equilibrium swelling percent (Seq %) and equilibrium water content percent (EWC %) were 1008 % and 90.97 %,respectively. The infrared spectrum of HBC-RH manifested significant functional groups such as hydroxyl (OH), carboxyl (COOH) and carbonyl group amide (CONH2) which strongly favor metal ion removal from aqueous solutions. The optimum solution pH value was 6.0 (0.84 mg/g) for arsenic and 8.0 (23.73 mg/g) for zinc. The increase of HBC-RH dosage from 0.167 to 10 g/L boosted up the removal of arsenic and zinc from 10.30 to 60.01 % and 48.30 to 95.32 %, respectively. Increase in arsenic uptake from 0.42 to 27.56 mg/g and zinc uptake from 7.81 to 32.69 mg/g were observed as the initial metal ion concentrations were varied from 1 to 150 mg/L at 28 ˚C and 1 g/L of HBCRH. A quick HBC-RH sorption of arsenic and zinc were realized within the initial 30 mins which was later followed by a slower sorption rate until equilibrium was achieved after 48 hrs for arsenic and 24 hrs for zinc. Langmuir isotherm best fitted the HBC-RH sorption of both metal contaminants and the maximum monolayer sorption capacity for arsenic and zinc were 41.32 mg/g and 32.47 mg/g, respectively. The kinetic data were best described by pseudo second-order. In light of the above results, HBC-RH can be considered a promising environmentalfriendly adsorbent for the removal of arsenic and zinc from aqueous media.